SIKAP DAN PERILAKU DOSEN RAHMATAN LIL 'ALAMIN - Herman Herman (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2019)
This article studies and analyzes the attitudes and behaviors of rahmatan lil ‘alamin lecturers in building Islamic character and culture of the students, the community and the environment. In the phenomenon emerging today, there are a number of lecturers who act and do in a normative-doctrinal concept which results in excessive apologetic attitudes (intellectual obstinacy). In addition, the soft skills in building and managing the rahmatan lil 'alamin students and community life is still very weak. Thus, it happens very often that they claim for unilateral truth justifying that they are the right one in interpreting Islam and accuse other groups as infidels and eretical orientalists. The final conclusion from this article is that the attitudes and behaviors of the rahmatan lil ‘alamin lecturers are potential to build Islamic character and culture in the students, community, and environment. Through experiences, performances and real works, responsibility and innovation, moderation, and uswah they will gradually bring advantages and benefits, solutions, and alternatives for the ummah to keep peace and tranquility, and are also consistent toward the change and renewal movement for the ummah and their environment.